2007
DOI: 10.1103/physrevc.76.064311
|View full text |Cite
|
Sign up to set email alerts
|

State-dependent calculation of three-body cluster energy for nuclear matter and the validity of the lowest order constrained variational formalism

Abstract: It is shown that the method of lowest order constrained variational (LOCV) which is based on the cluster expansion theory is a reliable many-body technique to calculate the nuclear matter equation of state. In this respect, the state dependent correlation functions and the effective interactions which have been produced by the LOCV calculation with the Reid and -Reid soft core interactions are used to estimate the size of higher order cluster terms such as the effect of three-body cluster energy on the nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 33 publications
(52 reference statements)
1
14
0
Order By: Relevance
“…But the inclusion of the three-body force and the isobar degrees of freedom ( -Reid68) [10,28,29,45,46] have improved the behavior of Coester line to the right direction [10,45,46]. For the convergence of LOCV [39,40] formalism and comparison of our result on nuclear matter with other many-body techniques, see Tables I and II of our works in [49][50][51].…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…But the inclusion of the three-body force and the isobar degrees of freedom ( -Reid68) [10,28,29,45,46] have improved the behavior of Coester line to the right direction [10,45,46]. For the convergence of LOCV [39,40] formalism and comparison of our result on nuclear matter with other many-body techniques, see Tables I and II of our works in [49][50][51].…”
Section: Introductionmentioning
confidence: 70%
“…But still, a reliable many-body technique and a true NN potential are needed to predict the results close the empirical nuclear matter properties. In several of our previous works it has been shown that the application of lowest order constrained variational method (LOCV) [28][29][30][31][32][33][34][35][36][37][38][39][40], to the different realistic phenomenological NN potentials [1][2][3][4][5][6][7][8][9][10][11][12], gives substantially too much binding and large saturation density than the empirical one. During the last three decades, situation has been the same for other techniques [10,[41][42][43][44][45][46][47][48] and potentials [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The two-body correlation operators, f (ij), which depend on the density, are defined as follows [21,34]: where for nuclear matter, as we pointed out before, α = {J LST } and the explicit form of V α (r, ρ) and a α (r, ρ) for Reid type and Av 18 potentials are given in Refs. [24][25][26][27]. The shapes of the above density-dependent effective interactions as well as the corresponding state-dependent versions can be found in the various works of Modarres et al [21][22][23][24][25][26][27][28].…”
Section: Appendix a The Locv Formalism And The Calculation Of Aei Fomentioning
confidence: 94%
“…A (S) is anti-symmetrizing (symmetrizing) operator [19][20][21][22][23][24][25][26]. In the cluster expansion technique [33], the expectation value of Hamiltonian of A-body system is written as:…”
Section: Appendix a The Locv Formalism And The Calculation Of Aei Fomentioning
confidence: 99%
See 1 more Smart Citation